The talent management based on the example of Military Sports Teams and Military Sports Training Centers - Łukasz Mariusz Malinowski (Nicolaus Copernicus University in Toruń, 2015)
The article concerns the problems of sourcing talent for Military Sports Training Centers, describes the financial support provided by the Ministry of Sport and Tourism. It also describes the operation and achievements of Polish Military Sports Teams.